2020
DOI: 10.1177/1538574420964644
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Type II Endoleak Treatment Using Ethylene Vinyl Alcohol Copolymer (OnyxTM)

Abstract: Introduction: This study reports our experience with the use of an ethylene vinyl alcohol copolymer (Onyx™) for the treatment of type II endoleak after endovascular repair of abdominal aortic aneurysms (EVAR) in comparison to coils and cyanoacrylate glue. Methods: Clinical data of all patients treated for type II endoleak following EVAR between 2009 and 2017 were retrospectively analyzed. Abdominal aortic aneurysm (AAA) diameter and AAA sac volume during follow-up were measured using computed tomography angiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
(54 reference statements)
1
4
0
Order By: Relevance
“…Association of the volume of Onyx used and the fracture and fragmentation phenomena we have documented is another venture for future study as the largest volume we used (46.5 ml) is 9.5 times the mean volume of 4.91 ml and more than double the largest volume of 21.0 ml reported in the study by Mozes et al 5 of 99 patients. Our numbers are fairly similar to the study reported by Nuckles et al 8 where our mean volumes are 13.6 ml compared to their 13.4 ml and our largest volumes are not too dissimilar at 46.5 ml compared to 39 ml in their series of 35 patients. Neither paper reports fragmentation on follow-up imaging, but the most dramatic change we observed were in the patients requiring larger volumes.…”
Section: Discussionsupporting
confidence: 92%
“…Association of the volume of Onyx used and the fracture and fragmentation phenomena we have documented is another venture for future study as the largest volume we used (46.5 ml) is 9.5 times the mean volume of 4.91 ml and more than double the largest volume of 21.0 ml reported in the study by Mozes et al 5 of 99 patients. Our numbers are fairly similar to the study reported by Nuckles et al 8 where our mean volumes are 13.6 ml compared to their 13.4 ml and our largest volumes are not too dissimilar at 46.5 ml compared to 39 ml in their series of 35 patients. Neither paper reports fragmentation on follow-up imaging, but the most dramatic change we observed were in the patients requiring larger volumes.…”
Section: Discussionsupporting
confidence: 92%
“…Among different approaches, endoleak treatment with coil embolization was widely used; however, it is associated with a high rate of endoleak recurrency. For the high reintervention rate, many investigators have refined their technique associating EVOH liquid agents with coils [ 47 ]. As shown by Ameli-Renani et al, since 2010, multiple scientific papers describing the use of liquid embolizing agents in treatment of Type I and II endoleaks have been published.…”
Section: Endoleakmentioning
confidence: 99%
“…Earlier literature reports the use of coils alone to embolize E2; more recently, multiple articles have reported the use of liquid embolic agents alone or in association with coils. A recent study [ 47 ] showed that there is no clinical or statistical difference between the treatment of EL with coils or with Onyx alone, in a population of 17 patients treated with Onyx alone vs. 18 patients treated with coils and glue (There were no significant differences between the two groups regarding age, BMI, or sex). In looking at comorbid conditions, there was no difference in the incidence of hypertension, hyperlipidemia, coronary artery disease, prior myocardial infarction, congestive heart failure, atrial fibrillation, tobacco use, diabetes mellitus, or chronic kidney disease, showing no statistical differences in clinical, efficacy, and safety.…”
Section: Endoleakmentioning
confidence: 99%
“…After over a decade of experience with translumbar embolization of endoleaks, 9 our group began transcaval embolization using a TIPS needle approach. Unfortunately, we were not satisfied with the rigidity and lack of maneuverability that arose with the use of the TIPS needle.…”
Section: Discussionmentioning
confidence: 99%